Improving Charcoal Briquette Production At Cv Hikmah Surabaya Arang, Parappe Village: A Technological Approach Using Briquette Molding Machines - Jasman, Dzulkifli; Andayani, Nining Diah; Rahman, Adiputra (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the charcoal briquette production system at CV Hikmah Surabaya Arang, located in Parappe Village, Campalagian Sub-district, Polewali Mandar Regency. The main focus of the research is the application of continuous screw molding machine technology to improve production efficiency. The background of this study reflects the urgent need for environmentally friendly alternative energy, as well as efficiency challenges faced by small enterprises based on biomass waste. A descriptive qualitative approach was employed, using data collection techniques such as field observations, in-depth interviews, and documentation. The results indicate that the use of the briquette molding machine contributed to a daily productivity increase of up to 50%, reduced working time, and ensured product consistency. In addition, there were positive social impacts, including increased income, redistribution of work tasks, and growing technological awareness among business actors. Identified constraints include limited drying infrastructure during the rainy season, lack of technical training, and fluctuations in raw material availability. Therefore, technology adoption must be accompanied by human resource capacity building, improvement of production facilities, and collaboration with external partners. The findings of this study are expected to serve as a reference for the development of more adaptive and sustainable local charcoal briquette enterprises.